2017
DOI: 10.1021/acs.langmuir.7b01368
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Pen Lithography with Lipids for Large-Area Gradient Patterns

Abstract: Gradient patterns comprising bioactive compounds over comparably (in regard to a cell size) large areas are key for many applications in the biomedical sector, in particular, for cell screening assays, guidance, and migration experiments. Polymer pen lithography (PPL) as an inherent highly parallel and large area technique has a great potential to serve in the fabrication of such patterns. We present strategies for the printing of functional phospholipid patterns via PPL that provide tunable feature size and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…This feature‐size dependence on force enabled by the compression of the polymeric tips is a distinguishing controllable parameter that is not realized in a classical DPN (Figure E). Utilizing this force‐dependent property, PPL can pattern combinatorial library of features from nanoscale to microscale over large areas by simply tilting the tip array . In recent years, Chen et al used PPL to create combinatorial libraries consisting of every combination of metallic elements (Au, Ag,Co, Cu, and Ni) through polymer nanoreactor‐mediated synthesis .…”
Section: Development Of Dpn and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature‐size dependence on force enabled by the compression of the polymeric tips is a distinguishing controllable parameter that is not realized in a classical DPN (Figure E). Utilizing this force‐dependent property, PPL can pattern combinatorial library of features from nanoscale to microscale over large areas by simply tilting the tip array . In recent years, Chen et al used PPL to create combinatorial libraries consisting of every combination of metallic elements (Au, Ag,Co, Cu, and Ni) through polymer nanoreactor‐mediated synthesis .…”
Section: Development Of Dpn and Its Derivativesmentioning
confidence: 99%
“…Utilizing this force-dependent property, PPL can pattern combinatorial library of features from nanoscale to microscale over large areas by simply tilting the tip array. [109,110] In recent years, Chen et al used PPL to create combinatorial libraries consisting of every combination of metallic elements (Au, Ag,Co, Cu, and Ni) through polymer nanoreactor-mediated synthesis. [111][112][113] Furthermore, the large area elastomeric tip array significantly increases the amount of ink adsorbed and enables multiple printing tasks without re-inking.…”
Section: Polymer Pen Lithographymentioning
confidence: 99%
“…to the support by tilting has been demonstrated to be a powerful way to print gradient patterns of molecules [74]. A summary of the different printing methodologies reported in this review can be found in Table 1, which specifically lists ink properties, such as viscosity and surface tension, printing resolution, and process characteristics (speed, resolution range, typical thicknesses, etc.).…”
Section: Dip Pen Nanolithographymentioning
confidence: 99%
“…It combines DPN and microcontact printing (µCP) features, by using an array of soft elastomeric tips (~10 6 pyramid-shaped tips), that can be brought into contact with the solid support and optically leveled for uniform patterning. Additionally, the possibility to control the relative position of the tip array with respect to the support by tilting has been demonstrated to be a powerful way to print gradient patterns of molecules [74]. A summary of the different printing methodologies reported in this review can be found in Table 1, which specifically lists ink properties, such as viscosity and surface tension, printing resolution, and process characteristics (speed, resolution range, typical thicknesses, etc.).…”
Section: 1zno Synthesis Approachesmentioning
confidence: 99%
“…The microarray within the microfluidic channel was printed via polymer pen lithography (PPL) . This technique combines aspects of microcontact printing and dip‐pen nanolithography (DPN) in a hybrid way and allows large area (several cm²) patterning, especially for sensitive, bioactive molecules in gradients and in a multiplexed fashion . This allows also easy integration into microfluidic systems as we demonstrated for the above‐mentioned application of CTC capture and mast cell screening, recently.…”
Section: Introductionmentioning
confidence: 99%